MUTED STANZAS: EXPLORING THE IMPACT OF ANXIETY AND RETICENCE ON LEARNING POETRY IN ESP CLASSES IN CHINA - Chen, Li Wei; Zhang , Jing Yi (International Research Journal of Arts and Communication, 2024)
Foreign language anxiety, a phenomenon extensively documented in literature (Horwitz et al., 1986; Kitano, 2001; Liu, 2006a, b; MacIntyre and Gardner, 1989; Phillips, 1992), continues to exert significant influence on language learners. This paper explores the multifaceted nature of foreign language anxiety, drawing on insights from various scholars. It delves into the myriad reasons behind language learners' reticence and reluctance to express ideas, particularly when speaking individually in class. Factors such as low language proficiency, fear of ridicule, concerns about losing face, interpersonal competition, personality traits, cultural norms, and generalized anxiety contribute to the prevalence of this phenomenon (Liu, 2006a, b; Jackson, 2002, 2003; Zou, 2004). The paper endeavors to shed light on the complex interplay of these factors and their impact on language learning experiences. By elucidating the underlying causes of foreign language anxiety, this paper aims to inform educators and practitioners about effective strategies to mitigate its effects and create supportive learning environments conducive to language acquisition.